Granulomatous lesions in a wild mullet population from the eastern Ligurian Sea (Italy): mycobacteriosis vs. pseudotuberculosis. Issue 6 (14th August 2013) - Varello, K; Prearo, M; Serracca, L; Meloni, D; Rossini, I; Righetti, M; Pezzolato, M; Fioravanti, M L; Ercolini, C; Bozzetta, E
Abstract Mycobacterium spp. and Photobacterium damselae subsp. piscicida are recognized as the most frequent causative agents of granulomatous lesions in fish. Although frequent episodes of mycobacterial infections have been reported in wild fish worldwide, only sporadic cases have been documented to date in Italy. To investigate for the presence of lesions referable to mycobacteriosis and to identify the mycobacterial species involved, a total of 159 wild mullets were fished from the eastern coast of the Ligurian Sea, killed and necropsied. Liver and spleen samples were collected from all fish for histopathological and microbiological analyses. Molecular investigations for identification of Photobacterium damselae subsp. piscicida were performed. Gross examination revealed granulomatous lesions in one animal; microscopically, 42.14% of fish displayed granulomas with various histological features, 19.50% resulted positive at Ziehl–Neelsen staining, and were confirmed as mycobacterial lesions by culture. The identified colonies were characterized as M. fortuitum, M. abscessus, M. flavescens, M. chelonae, M. septicum and M. nonchromogenicum. In all, 35% of animals resulted positive for Photobacterium damselae subsp. piscicida. These data suggest widespread mycobacterial infection also by Photobacterium damselae subsp. piscicida infections in wild fish. Moreover, the pathogenicity of some mycobacterial species, previously considered as saprophytic, was demonstrated.